2017
DOI: 10.1007/s10461-017-1732-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Use of Safer Conception Methods in a Prospective Cohort of Ugandan HIV-Affected Couples with Fertility Intentions

Abstract: We examined the prevalence and correlates of safer conception methods (SCM) use in HIV-affected couples with fertility intentions. A prospective cohort of 400 HIV clients in Uganda who had fertility intentions with their partner was surveyed every 6 months for 24 months. Logistic regression analysis was used to determine individual, relationship and provider level predictors of SCM use. Over one-third (35%) reported any use of timed unprotected intercourse (TUI) during the study; use of other SCM was rare. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Factors affecting SCS availability from the individual or couple’s perspective included lack of awareness about safer conception services [20, 22, 33, 3642] and limited integration of services for sexual and reproductive health into HIV care [4345]. Few patients discussed fertility goals with providers, and discussions around pregnancy focused on maternal and child health and not on sexual HIV transmission [3941, 46].…”
Section: Resultsmentioning
confidence: 99%
“…Factors affecting SCS availability from the individual or couple’s perspective included lack of awareness about safer conception services [20, 22, 33, 3642] and limited integration of services for sexual and reproductive health into HIV care [4345]. Few patients discussed fertility goals with providers, and discussions around pregnancy focused on maternal and child health and not on sexual HIV transmission [3941, 46].…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted at two sites within The AIDS Support Organization (TASO) in Uganda [ 18 , 19 ]. TASO Kampala located next to the Mulago National Referral Hospital and TASO Jinja within the Jinja Regional Referral Hospital in Jinja district.…”
Section: Main Textmentioning
confidence: 99%
“…The primary study from which these data were derived included 400 PLHIV in care (including 299 HIV-infected women) and was powered to evaluate the use of use of safer conception methods [ 18 ]. The current analysis includes 127 women who reported at least one pregnancy within the 24 months of follow-up.…”
Section: Main Textmentioning
confidence: 99%
“…[15] Our research revealed individual (low SCM awareness; internalized childbearing stigma), partner (HIV non-disclosure; partner willingness to use SCM or attend SCC), and provider (childbearing stigma; lack of SCC knowledge and training) level barriers to SCM use. [14,16] Our prior research also suggests that HIV-serodiscordant couples who are considering childbearing may decide to delay pregnancy, especially if both members are not certain about wanting a child or if health concerns need to rst be resolved. [17] However, studies that have examined fertility desires among PLHIV have often neglected to measure contraception use and intentions.…”
Section: Introductionmentioning
confidence: 99%